RELOCATION OF AFTERSHOCK HYPOCENTER PERIOD 7-10 JUNE 2006 FROM YOGYAKARTA EARTHQUAKE MAY 27, 2006, USING THE DOUBLE-DIFFERENCE METHOD WITH DETERMINATION OF LOCAL MAGNITUDE - Irawan, Feri
On May 27, 2006, a strong earthquake shook several regions in the Special Region of Yogyakarta and Central Java for approximately 60 seconds with a magnitude of 6.3 Mw. This earthquake is considered to have occurred due to the movement of the Opak Fault. However, previous studies have shown that the hypocenter aftershocks due to the May 2006 Yogyakarta earthquake are located about 10 kilometres east of the Opak Fault (Walter et al., 2008). This study improves the straightness of the hypocenter aftershocks in period 7 to 10 June 2006 to emphasize the alignment of the Yogyakarta earthquake in May 2006. The update in this study is to retrieve the P and S waves, relocation using the double-difference method supported by the use of the waveform cross-correlation method. This research also determines the local magnitude. From the results obtained, there were three hypocenter clusters obtained by the fault that was activated by the Yogyakarta earthquake in May 2006. Also, there was a decrease in the value of the local magnitude.